2019
DOI: 10.1002/adfm.201905247
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylonitrile Interactions with Carbon Nanotubes in Solution: Conformations and Binding as a Function of Solvent, Temperature, and Concentration

Abstract: Polyacrylonitrile (PAN) is among the most promising precursor polymers to produce strong and lightweight carbon fiber. Conformations in solution and the extent of binding to carbon nanotubes (CNTs) are critical during gel spinning and for alignment of graphitic layers upon carbonization. First quantitative insights into these processes are reported using molecular dynamics simulations from the atomic scale including virtual π electrons and comparisons to experimental data. Common solvents for fiber spinning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 87 publications
(104 reference statements)
2
16
0
Order By: Relevance
“…Implementation of recent models with improved representations of π-electrons in aromatic rings would enhance the molecular interpretation of our experimental results and improve correlations obtained from simulations presented herein . Recent work by Pramanik et al, showed that through the implementation of such models, better correlations of polymer binding to carbon nanotubes were achieved relative to simple atomistic models . Overall, the binding energy discussion lets us conclude that the measured IFA fluctuation energies correspond to the molecular adhesive energies between the peptides and graphite, and that the amino acid sequence plays a prominent role in the interaction of the peptides with graphene.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Implementation of recent models with improved representations of π-electrons in aromatic rings would enhance the molecular interpretation of our experimental results and improve correlations obtained from simulations presented herein . Recent work by Pramanik et al, showed that through the implementation of such models, better correlations of polymer binding to carbon nanotubes were achieved relative to simple atomistic models . Overall, the binding energy discussion lets us conclude that the measured IFA fluctuation energies correspond to the molecular adhesive energies between the peptides and graphite, and that the amino acid sequence plays a prominent role in the interaction of the peptides with graphene.…”
Section: Resultssupporting
confidence: 62%
“…51 Recent work by Pramanik et al, showed that through the implementation of such models, better correlations of polymer binding to carbon nanotubes were achieved relative to simple atomistic models. 52 Overall, the binding energy discussion lets us conclude that the measured IFA fluctuation energies correspond to the molecular adhesive energies between the peptides and graphite, and that the amino acid sequence plays a prominent role in the interaction of the peptides with graphene.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…In those models, we neglected the influence of π-electrons of graphene-related materials, although the polarity of carbon nanotubes affected the interactions of polar molecules and ions . The INTERFACE force field has virtual π-electrons, which is adopted for description of carbon nanotubes. , π-interaction plays one of the major roles in polymer and solvent interactions with carbon nanotube surfaces. An interaction between an ion and π-electrons of a carbon nanotube was considerable for ion adsorption, while an interaction between water and the π-electrons was weak.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…44 The INTERFACE force field has virtual π-electrons, which is adopted for description of carbon nanotubes. 45,46 π-interaction plays one of the major roles in polymer and solvent interactions with carbon nanotube surfaces. An interaction between an ion and π-electrons of a carbon nanotube was considerable for ion adsorption, while an interaction between water and the π-electrons was weak.…”
Section: Methodsmentioning
confidence: 99%
“…The advantages of these techniques include insight at the scale of atoms, access to the large nanometer scale, and the ability to simulate entire stress-strain experiments from equilibrium to failure in high accuracy. [6] [7] Simulations then allow to design and screen a larger number of model structures with a variety of defects and nanoscale features of interest, inspired by experimental data and theory, and examine the failure mechanisms in depth. However, although more efficient than experiments, the computational cost is still considerable.…”
Section: Introductionmentioning
confidence: 99%